PRELIMINARY GEOCHRONOLOGICAL STUDY OF GRANULITES FROM THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA : A COMPARISON OF Rb-Sr AND Sm-Nd AGES - シライシ, カズユキ; カガミ, ヒロオ; SHIRAISHI, Kazuyuki; KAGAMI, Hiroo (National Institute of Polar Research, 1989)
P(論文) We report the preliminary results of whole-rock Rb-Sr and Sm-Nd isochrons dating on granulite-facies metamorphic rocks from Brattnipene, central Sør Rondane Mountains, East Antarctica. Samples : Isotopic ratios of eight samples were measured with a MAT 261 mass spectrometer at the Institute for Study of the Earth's Interior, Okayama University. Four samples are enderbites consisting of Opx, Cpx, Hbl, Bt, Pl and Qtz with or without Grt and Kfs (mineral abbreviations after R. KRETZ : Am. Mineral., 68,277,1983). These rocks were collected within a hundred meters of each other. The other four samples are hornblende gneisses as follows : Bt-Hbl-Pl, Bt-Hbl-Kfs-Pl-Qtz, Cpx-Hbl-Pl-Qtz and Bt-Hbl-Pl-Qtz. Two of them have been slightly altered to form secondary epidote and/or bluish green hornblende. All samples crop out within 500m. The peak metamorphic conditions of the enderbites were estimated from geothermobarometry to be 800℃ and 7-8.5kb (K. SHIRAISHI and S. KOJIMA : Proc. NIPR Symp. Antarct. Geosci., 1,129,1987). The hornblende gneisses were presumably metamorphosed under the same conditions. Rb-Sr data : The ^<87>Rb/^<86>Sr ratios for eight samples are low (0.02-0.15) and no meaningful isochron can be drawn due to the considerable scattering of the data. Four enderbites, however, define an isochron of 1167±127 Ma with initial ratio 0.7040. Sm-Nd data : The ^<143>Nd/^<144>Nd vs. ^<147>Sm/^<144>Nd ratios for all eight samples defined an isochron of 999±164 Ma with an initial ratio of 0.51158. The calculated uncertainty is high because the spread of the ^<147>Sm/^<144>Nd ratios is limited. T_<(DM)> model ages (ε_<ND(0)>=+10) range between 1150 and 1300 Ma.Previous work has shown that the region was affected by a thermal event associated with plutonism about 500Ma ago. This event may be the cause of the scatter in the Rb-Sr data. Nonetheless, four enderbites, which seem to be fresh under the microscope, yield a Rb-Sr isochron whose age is consistent ...